Inflammatory and traditional risk factors associated with the progression of chronic kidney disease in patients with rheumatoid arthritis - Masafumi Sugiyama; Sayo Morita; Takashi Tsuchimoto; Saki Tsuchimoto; Chise Minami; Koji Kinoshita; Shinya Rai (Clinical and Experimental Nephrology, 2026)
Abstract Background Chronic kidney disease (CKD) is a significant comorbidity in patients with rheumatoid arthritis (RA). The relative contributions of inflammatory and traditional renal risk factors to CKD progression remain unclear. Methodology We retrospectively analyzed 601 RA patients. Renal function and urinary abnormalities were assessed using creatinine-based estimated glomerular filtration rate (eGFR) and urinary albumin. We examined the factors associated with high or very high CKD risk in KDIGO heatmap and progression of CKD stage over five years using two models: logistic regression and Cox proportional hazards models. Furthermore, Propensity score methods were used to assess the association between methotrexate (MTX) use and CKD stage progression . Results CKD stage progression occurred in 106 patients. Both inflammatory and traditional renal risk factors were associated with high or very high CKD risk. In Cox analyses, age, lower baseline eGFR, anemia, and CRP ≥0.5 mg/dL were associated with CKD stage progression. In patients with baseline eGFR ≥60 mL/min/1.73 m 2 , CRP ≥0.5 mg/dL was independently associated with progression, whereas proteinuria and albuminuria were more relevant in patients with baseline eGFR